KEBAHAGIAAN PADA WANITA DEWASA MADYA YANG MELAJANG - Sindhy Mariam Magdalena Pello; Christiana Hari Soetjiningsih (PSIKOLOGI KONSELING, 2020)
Happiness is a concept that relate to the emotion and positive activities felt by each individual except for the single people. The purpose of this research is to know the illustration of happiness to the adult females who decided to remain single and the influenced factors of happiness. Qualitative research method is used with phenomenological approach. The participants of this research are two adults’ females 40-65 years old who decided to remain single. Interpretative phenomenological analysis (IPA) is used for the data analysis technique. The results of this research showed that adults females who decided to remain single still felt happiness through the positive relationship with others by doing things or activities that they liked, finding the meaning of their days, and having optimism and resilience attitude. The most influenced factor of happiness is religiosity. Keywords: Happiness; Adult Female; Single; Religiousity; Success.